The enquiries of conventional architectural education - Abdullah, Fadzidah; Abdul Rahim, Asiah (Common Ground Publishing LLC, 2009)
Although the conventional architectural educational approach has been used by most schools of architecture for more than a hundred years, and recognised by scholars as being a “good” experiential learning method, it is also criticised as having a weakness and its irrelevancy to the current architectural education is being harrowing. Through decades of its evolution, architectural education has been confronted with many wide-ranging critiques, discussed in such occasions as architectural conferences, architectural accreditation meetings, in printed media such as journals and reports, and formal and informal faculty discussions. Critical comments are expressed as responses to the disappointment arising from many parties involved in the construction industry that architectural graduates do not perform as expected of them. In fact, the architectural profession was shocked by the intensity of the critical comment it received on inadequacies of architects’ performance.